A process capacity index for multivariate non-normal distributions of correlated and uncorrelated variables - Salazar, Erasmo Rafael (2017)
In the multivariate analysis of capacity there are many aspects, not even resolved yet, around some indexes such as the non-normality of the data and if the variables of quality are correlated or not. In this work we intend to propose the development of a multivariate capacity index (ICPM, for its acronym in Spanish) that works for both previous cases through simulated data examples. It is worth mentioning that we find a wide performance of the proposed index in comparison with other similar capacity indexes.